(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the effectiveness of the implementation of Article 24 of the Income Tax Law in avoiding international double taxation and to identify administrative and technical barriers faced by taxpayers. Double taxation occurs when income is taxed in more than one country, thus burdening entities that carry out cross-border activities. In Indonesia, Article 24 provides a foreign tax credit mechanism as a solution to prevent double taxation. The research method uses a descriptive qualitative approach with literature studies and simulative case studies on taxpayer entities that receive income from abroad. The results of the study indicate that the provisions of Article 24 are quite effectively implemented, as long as taxpayers can meet the administrative requirements, including proof of tax deductions from the source country. However, challenges still arise, such as differences in taxation systems between countries, limited documentation, and low tax literacy.